Investigation of the Effect of Different Seed Flours on Gluten-Free Products: Baton Cake Production, Characterization, and TOPSIS Application - Dedebas, Tugba; Cebi, Nur (MDPI, 2024)
The present study aims to develop gluten-free product formulations by using different seed flours to determine their effectiveness in gluten-free products. For this purpose, a baton cake model was selected; the cake production process was conducted by adding hemp, okra, mustard, or coriander seed flours with rice flour at a ratio of 25% seed flour to 75% rice flour to prepare the cake batters. The physicochemical, textural, and sensory properties, as well as the baking behaviors of the resulting products, were determined. The TOPSIS method was used in the sensory analyses. With the addition of seed flours, a color change occurred in the inner and crust values of the baton cake samples. It was observed that the hardness value of the baton cake samples increased with the addition of seed flour. In the TOPSIS evaluation, which is a multi-criteria decision-making method, the most preferred product in the free baton cake samples was the cake with hemp seed flour added, while the least preferred product was the control group baton cake. According to the findings, it was concluded that the use of seed flours can be used as an alternative ingredient in the production of gluten-free baton cakes that celiac patients can consume in their diets.
Keywords: seed flour; gluten-free; baton cake; texture; sensory; TOPSIS; PHYSICOCHEMICAL PROPERTIES; FUNCTIONAL-PROPERTIES; ANTIOXIDANT; COMPONENT; BREAD; Food Science & Technology